Genetic analysis of maize genotypes possessing novel combination of opaque2 and opaque16 genes affecting higher accumulation of lysine and tryptophan in kernels. (September 2022) - Chand, Gulab; Zunjare, Rajkumar U.; Allen, Tanu; Muthusamy, Vignesh; Mishra, Subhra J.; Kasana, Ravindra K.; Bhatt, Vinay; Ismail, Mohammad Reda; Sarika, Konsam; Guleria, Satish K.; Hossain, Firoz
Abstract: Traditional maize protein is nutritionally poor due to low levels of lysine (0.150–0.250%) and tryptophan (0.030–0.040%). The recessive opaque2 ( o2 ) gene that enhances lysine (0.300–0.400%) and tryptophan (0.070–0.100%) is used in developing quality protein maize hybrids. Mutant opaque16 ( o16 ) in the presence of o2 further enhances lysine and tryptophan. Here we analyzed a set of seven diverse maize inbreds possessing o2 and o16 for their potential to develop heterotic hybrids. Characterization of inbreds using 75 SSRs revealed 177 alleles with wide variation in dissimilarity coefficient (0.34–0.80). Phylogenetic analysis grouped the o2o2/o16o16 -based inbreds into three clusters. Inbreds were further crossed in a half-diallel mating design, resulting in 21 experimental hybrids were evaluated at two locations. Experimental o2o2/o16o16 -based hybrids possessed significantly higher lysine (0.506%) and tryptophan (0.126%) compared to commercial o2 -based QPM hybrids (lysine: 0.346%, tryptophan: 0.086%). Combining ability for grain yield identified several promising inbreds and hybrids. Grain yield was significantly correlated with genetic distance (r = 0.57**) and SCA effect (r = 0.67**). Selected hybrids with >7500 kg/ha grain yield, >0.500% lysine and >0.120% tryptophan possess great potential in providing both food- and nutritional-security. The improved hybrids with a novel combination of o2 and o16 provide sustainable and cost-effective solution to alleviate protein energy malnutrition. Graphical abstract: Image 1 Highlights: Inbreds with o2o2/o16o16 revealed wide genetic diversity. Phylogenetic analysis grouped the o2o2/o16o16 -based inbreds into three clusters. o2o2/o16o16 -based hybrids possessed significantly higher lysine and tryptophan. Combining ability identified promising o2o2/o16o16 -based inbreds and hybrids. Grain yield was significantly correlated with genetic distance and SCA effect.